PENGEMBANGAN VIDEO PEMBELAJARAN STATISTIKA BERBASIS VOKASI - I Wayan Sumandya (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
This study aims to obtain a vocational-based statistics learning video that is valid, practical and effective. The research was conducted at SMK Wira Harapan. The type of research used is research and development (Research and Development). The research and development steps are guided by the ADDIE model consisting of: Analysis, Design, Development, Implementation, and Evaluation. The results obtained in this study are valid, practical and effective quality-based vocational statistics learning videos. Based on the evaluation of material experts, the average score is 3.60 and 3.55 for expert learning, including the